Analytical solutions to heat transfer equations by homotopy-perturbation method revisited - Chowdhury, Md. Sazzad Hossien; Hashim, Ishak (Elsevier, 2008)
In this Letter, the problem of determining the temperature distribution of a straight rectangular fin with power-law temperature-dependent surface heat flux is revisited. The solution of the corresponding nonlinear boundary-value problem (BVP) based on the homotopy-perturbation method (HPM) presented earlier is corrected and extended.